INDONESIAN FOOD INDUSTRY ON HALAL SUPPLY CHAINS - Hadi Peristiwo (University of Sultan Ageng Tirtayasa, 2020)
Halal food industry is one of the potential economic sectors. This industry is experiencing a rapid global development. Indonesia is a country with the most Muslim population in the world. In addition, this country also has various potentials great in developing the halal food industry on the global scene. However, various existing problems and forms of regulation make Indonesia still unable to compete with other countries. Therefore, this review tries to explore various opportunities and the challenges of the halal food industry at Indonesian, especially in terms of the halal supply chain at industrial revolution 4.0. The method used is library research using a variety of secondary sources as research material.